2022
DOI: 10.1371/journal.pgph.0000551
|View full text |Cite
|
Sign up to set email alerts
|

A syndemic born of war: Combining intersectionality and structural violence to explore the biosocial interactions of neglected tropical diseases, disability and mental distress in Liberia

Abstract: The intersections between NTDs, disability, and mental ill-health are increasingly recognised globally. Chronic morbidity resultant from many NTDs, particularly those affecting the skin—including lymphatic filariasis (LF), leprosy, Buruli ulcer (BU) and onchocerciasis—is well known and largely documented from a medicalised perspective. However less is known about the complex biosocial interaction shaping interconnected morbidities. We apply syndemic theory to explain the biosocial relationship between NTDs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Although MDA has proven its benefits in diminishing transmission rates of several PC-NTDs in many areas, over years of implementation, this measure cannot be expected solve all problems arising from these diseases. Relying solely on ‘magic bullet’ interventions, which are expected to solve multifactorial ‘syndemics’48 including social problems like stigma and poverty, can have unforeseen consequences. Multifactorial issues require multifaceted solutions, and the cost-effectiveness of drug distributions should not overshadow the need for alternative measures addressing socioecological determinants of ill health 49.…”
Section: Discussionmentioning
confidence: 99%
“…Although MDA has proven its benefits in diminishing transmission rates of several PC-NTDs in many areas, over years of implementation, this measure cannot be expected solve all problems arising from these diseases. Relying solely on ‘magic bullet’ interventions, which are expected to solve multifactorial ‘syndemics’48 including social problems like stigma and poverty, can have unforeseen consequences. Multifactorial issues require multifaceted solutions, and the cost-effectiveness of drug distributions should not overshadow the need for alternative measures addressing socioecological determinants of ill health 49.…”
Section: Discussionmentioning
confidence: 99%
“…For demographic factors, we find that male-headed households were less likely to have improved drinking water sources in comparison to their female-headed counterparts (OR = 0.86, p<0.001). In addition, older households (i.e., 40-49 and 50+) were less likely to have improved drinking water sources and sanitation facilities, compared to the youngest cohort (i.e., [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Similarly, married, widowed, and divorced households were all less likely to have improved drinking water sources and sanitation facilities, compared to their single counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…We fully adjusted for socioeconomic, geographical, and demographic factors in Model 3 and found that the patterns observed in Models 1 and 2 remained largely robust in terms of statistical significance. For demographic factors, it is interesting that older households -i.e., 40-49 (OR = 0.87, p<0.05) and 50+ (OR = 0.84, p<0.05)-were less likely to have improved drinking water sources, compared to the youngest cohort (i.e., [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Plos Watermentioning
confidence: 99%
See 1 more Smart Citation
“…6 Conflicts, political instability and weakened health and social systems often augment mental distress, which is compounded by stigma and discrimination among people affected by skin NTDs. 7 The DRC carries one of the highest burdens of leprosy within sub-Saharan Africa, with limited detailed information available regarding the prevalence of other endemic NTDs. 8 , 9 In 2022, 3032 new cases of leprosy were detected, of which 317 were already disabled at diagnosis.…”
Section: Introductionmentioning
confidence: 99%